PENGGUNAAN ALAT BANTU MENGAJAR DAN HUBUNGANNYA DENGAN PENCAPAIAN KEMAHIRAN MENDENGAR BAHASA ARAB (Sains Humanika, 2008)
The aims of this study are to identify the practice of Arabic listening teaching technique in teaching Arabic, to identify the use of the teaching aids in teaching Arabic, to identify the level of Arabic listening skills, and lastly to identify the differences of Arabic listening skills between students who were exposed and students who were not exposed to the teaching aids. This study used the cross sectional research design and employed two sets of questionnaires for students and one set of Arabic listening test. The results showed that the practice of Arabic listening teaching technique in teaching Arabic was at the low level; the use of teaching aids in teaching Arabic was also at the low level; the Arabic listening skills was however at the moderate level; and there was a significant difference in Arabic listening achievement between students who were exposed and students who were not exposed to the teaching aids.
Keywords: Arabic language listening skills; teaching of Arabic language listening skills; teaching aids material